2018
DOI: 10.3991/ijim.v12i4.8715
|View full text |Cite
|
Sign up to set email alerts
|

Development of Smartphone Application Based on the Theory of Planned Behaviour to Enhance Self-Efficacy for Online Learning

Abstract: This study was conducted to develop a smartphone application to enhance self-efficacy for online learning. The theory of planned behaviour (TPB) was used as a framework for developing the smartphone app. The study used research and design (R&amp;D) through three phases: 1)<strong> </strong>examining relevant literature and interviewing recognized experts in the field, 2) developing the smartphone app, and 3) studying the effect of the smartphone app on the self-efficacy of online learners. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 22 publications
(25 reference statements)
3
10
1
2
Order By: Relevance
“…According to theory of planned behaviour (TPB), this theory encompasses three main constructs: attitude towards the behaviour, subjective norm and perceived behavioural control (Klehe, 2018;Peechapol, Na-songkhla, Sujiva, & Luangsodsai, 2018;Radovanovic & Rus-Makovec, 2018;Seow, Choong, Moorthy, & Chan, 2017). In line with this study, attitude is able to predict a person's intention towards a specific behaviour.…”
Section: Theory Of Planned Behavioursupporting
confidence: 63%
“…According to theory of planned behaviour (TPB), this theory encompasses three main constructs: attitude towards the behaviour, subjective norm and perceived behavioural control (Klehe, 2018;Peechapol, Na-songkhla, Sujiva, & Luangsodsai, 2018;Radovanovic & Rus-Makovec, 2018;Seow, Choong, Moorthy, & Chan, 2017). In line with this study, attitude is able to predict a person's intention towards a specific behaviour.…”
Section: Theory Of Planned Behavioursupporting
confidence: 63%
“…In addition, Gikas and Grant reported that students had variety in learning, and situated learning. Our findings are also similar to various other studies [21,38]. Consistent with another recent qualitative study [21], the range of advantages might also include: Knowledge sharing and communication, useful and easy to learn, and personal goal setting.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings are also similar to various other studies [21,38]. Consistent with another recent qualitative study [21], the range of advantages might also include: Knowledge sharing and communication, useful and easy to learn, and personal goal setting. Such components could be fully explored in future research, and further enhancement of the application could include facilitated e-communication between the learners, as well as between the learners and the educator, and inclusion of self-monitoring of personal learning goals within the application.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations